Association of plasma growth arrest-specific protein 6 (Gas6) concentrations with albuminuria in patients with type 2 diabetes*. (June 2014) - Erek-Toprak, Aybala; Bingol-Ozakpinar, Ozlem; Karaca, Zeynep; Cikrikcioglu, Mehmet Ali; Hursitoglu, Mehmet; Uras, Ahmet Riza; Adeli, Khosrow; Uras, Fikriye
Abstract Aims: New biomarkers are required to detect diabetic nephropathy earlier in persons with type 2 diabetes mellitus. Recent experimental studies indicate that growth arrest-specific protein 6 (Gas6) may have a role in pathogenesis of complications associated with diabetes. The objective of the current study is to examine whether plasma Gas6 concentrations are associated with albuminuria in persons with type 2 diabetes mellitus. Methods: About 32 patients with diabetes which have micro or macroalbuminuria, 37 patients with diabetes and normoalbuminuria, and 30 healthy volunteers were recruited. Plasma Gas6 levels were measured by ELISA. Hemoglobin A1c (HbA1c), serum C reactive protein, fibrinogen and 24-h urine samples for microalbuminuria were analyzed by Primus PDQ, Beckman Coulter Immage 800, STA Compact and Roche Cobas Integra 800 analyzer, respectively. Statistical analysis was performed using SPSS (Statistical Package for Social Sciences) for Windows 11.5. Results: There was a noteworthy difference among the three groups for Gas6 according to the Kruskal–Wallis test (p < 0.01). Plasma Gas6 concentrations were higher in patients with micro or macroalbuminuria [20.9 ng/mL (16.7–27.0); median (25–75% percentile)] compared to patients with normoalbuminuria [16.5 ng/mL (13.1–22.9)], and healthy controls [15.3 ng/mL (8.3–33.6)]. Conclusions: In conclusion, this is the first study indicating that plasma Gas6 levels are associated with albuminuria in patients with type 2 diabetes. This study could be considered a starting point to focus on the association between Gas6 and diabetic nephropathy.